Luminographic Detection of von Willebrand Factor Multimers in Agarose Gels and on Nitrocellulose Membranes - Budde, U; Schneppenheim, R; Plendl, H; Dent, J; Ruggeri, Z M; Zimmerman, T S (Thrombosis and Haemostasis, 1990)
Two methods for visualization of vWf multimers were compared with respect to sensitivity and detection of normal vWf and vWd variants IIA, IIB, IIC, IID, HE, and HE Autoradiography and luminography after electrotransfer of vWf multimers onto nitrocellulose showed comparable sensitivity with vWf: Ag detectable after 1:500 dilution of normal plasma. The least sensitive method was luminography in agarose gels with vWf: Ag detectable after 1:300dilution of normal plasma. No difference existed in the banding patterns of plasmas from patients with variant vWd.